Complete chloroplast genomes of three wild perennial Hordeum species from Central Asia: genome structure, mutation hotspot, phylogenetic relationships, and comparative analysis - Yuan, Shuai; Nie, Cong; Jia, Shangang; Liu, Tianqi; Zhao, Junming; Peng, Jinghan; Kong, Weixia; Liu, Wei; Gou, Wenlong; Lei, Xiong; Xiong, Yi; Xiong, Yanli; et al. (Frontiers in Plant Science, 2023)
Hordeum L. is widely distributed in mountain or plateau of subtropical and warm temperate regions around the world. Three wild perennial Hordeum species, including H. bogdanii, H. brevisubulatum, and H. violaceum, have been used as forage and for grassland ecological restoration in high-altitude areas in recent years. To date, the degree of interspecies sequence variation in the three Hordeum species within existing gene pools is still not well-defined. Herein, we sequenced and assembled chloroplast (cp) genomes of the three species. The results revealed that the cp genome of H. bogdanii showed certain sequence variations compared with the cp genomes of the other two species (H. brevisubulatum and H. violaceum), and the latter two were characterized by a higher relative affinity. Parity rule 2 plot (PR2) analysis illuminated that most genes of all ten Hordeum species were concentrated in nucleotide T and G. Numerous single nucleotide polymorphism (SNP) and insertion/deletion (In/Del) events were detected in the three Hordeum species. A series of hotspots regions (tRNA-GGU ~ tRNA-GCA, tRNA-UGU ~ ndhJ, psbE ~ rps18, ndhF ~ tRNA-UAG, etc.) were identified by mVISTA procedures, and the five highly polymorphic genes (tRNA-UGC, tRNA-UAA, tRNA-UUU, tRNA-UAC, and ndhA) were proved by the nucleotide diversity (Pi). Although the distribution and existence of cp simple sequence repeats (cpSSRs) were predicted in the three Hordeum cp genomes, no rearrangement was found between them. A similar phenomenon has been found in the cp genome of the other seven Hordeum species, which has been published so far. In addition, evolutionary relationships were reappraised based on the currently reported cp genome of Hordeum L. This articlestudy offers provides a theoretical framework basis for gaining aa betterdeeper understanding of the evolutionary historygenome evolution of Hordeum species through the re-This is a provisional file, not the final typeset article examination of their cp genomes, and by identifying highly polymorphic genes and hotspot regions that could provide important insights into the genetic diversity and differentiation of these species..